Finnish citizens’ concerns about various dimensions of agricultural policy - Partio, Hanna; Pouta, Eija; Kuhmonen, Tuomas (European Association of Agricultural Economists (EAAE), 2014)
During the last decade, citizens have put a lot of attention to agricultural policy dimensions like multifunctionality, animal welfare, food safety, food security and environmental issues. Based on quantitative survey data set (n=1,623), this research examines Finnish citizens ́ concerns about various dimensions of agricultural policy. Principal component analysis resulted in a solution of four components. It seems that most worries by citizens relate to policy dimensions, which may cause personal risks in a long-term and which lie beyond personal control. Concerns that are more distant were not very worrying.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; agricultural policy dimensions; citizens; public concern